Penyebab Peserta Didik Tidak Berpartisipasi Aktif dalam Pembelajaran Sosiologi di Kelas XI IPS 1 SMAN 4 Merangin Jambi - Risanatul Risanatul; Junaidi Junaidi (Naradidik: Journal of Education and Pedagogy, 2022)
This research was motivated by the low level of participatory students in learning sociology in class XI social studies 1, SMA N 4 Merangin Jambi. This is evidenced by only 27.30% of students who play an active role in learning. From the percentage of active students, it shows that the level of student participation in learning is still low. The theory put forward in this study is the behavioristic theory according to skinner which focuses on the creation of behavioral patterns that can be seen from learning outcomes. The purpose of this study analyle out the causes of students not participatory in learning. This research uses a qualitative approach with a case study type of research. Informant selection technique using purposive sampling technique with the number of informants as many as 13 people. Data collection techniques are observation techniques, in-depth interviews and documentation studies. Data analysis uses Miles and Huberman's interactive analysis model which consists of data reduction, data presentation, and drawing conclusions. The results of this study show that there are several things that cause students not to participate in learning. The causes of class XI social studies students of SMAN 4 Merangin not actively participating: 1) fear or shame of being laughed at by friends. 2) don't understand metering. 3) the student's health condition 4) the curator's concentration is studying 5) the curator is self-preparation.